O gesto musical na interpretação de três obras para trombone de Estércio Marquez Cunha - Ângelo, Jackes Douglas Nunes (2015)
This article is result from combination of interpretive practice, bibliographic study into musical gesture, analysis of the interpreted musical works, and reporting my experience as interpreter. Is made here a gesture study in musical performance and its possible potential to optimize the interpretative communication between performer and pubic. For this, we used three music pieces for trombone by composer Estércio Marquez Cunha. Backed in bibliographical searches as well as in my experience report into the preparation and interpretation of the musical works, this research describes the relationship between performance and musical gesture. From the interpretative analysis, it was found multiple instances in which musical gesture, coupled with body movement, likely to influence the interpreter expressiveness, interfering therefore directly at the moment of performance.